Circular RNAs: Functions and Clinical Significance in Cardiovascular Disease - Zhang, Lei; Zhang, Yuan; Wang, Yin; Zhao, Yanfang; Ding, Han; Li, Peifeng (Frontiers in Cell and Developmental Biology, 2020)
Cardiovascular disease (CVD) causes high morbidity and mortality worldwide. Accumulating research has indicated the possible roles played by circular RNAs (circRNAs) in the pathogenesis of CVD. CircRNAs are noncoding RNAs with covalently closed loop structures. CircRNAs can function through by acting as miRNA sponges, RNA binding protein sponges, mRNA transcriptional regulators and templates for protein translation. The specific characteristics of circRNAs such as high stability, abundant distribution, and tissue- and developmental stage-specific expression make them potential biomarkers for the diagnosis and prognosis of CVD. In this paper, we systematically summarized the current knowledge regarding the biogenesis, biological properties and the action mechanisms of circular RNAs, elucidated the roles played by circRNAs in the pathogenesis of CVD, and explored the diagnostic potential of circRNAs in CVD. With in-depth studies, an increasing number of molecular mechanisms underlying the participation of circRNAs in CVD may be elucidated, and the application of circRNAs in the clinical diagnosis and prevention of CVD may eventually be realized.